Bilateral Mastoid Process Hypertrophy Associated With Severe Trismus. Issue 4 (15th June 2021) - Sent-Doux, Kimberley; Moore, Mark H.; Tan, Swee T.
Abstract : Abstract: The mastoid process, a pneumatized prominence of the temporal bone with air-filled air cells, grows with age. We present here a series of 4 patients with bilateral mastoid hypertrophy associated with severe trismus from different etiologies, and discuss the possible explanation of this observation.